2016
DOI: 10.1016/j.humimm.2016.07.007
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of CD39 as a novel immunoregulatory mechanism invoked by COPD

Abstract: Acute exacerbations of chronic obstructive pulmonary disease (AECOPD) are characterized by increased pulmonary and systemic inflammation and commonly caused by bacterial and/or viral infection. Little is known about the T-cell dysregulation in AECOPD that promotes these outcomes.CD39 is an ectonucleotidase able to hydrolyse adenosine triphosphate to create adenosine that may inhibit T-cell responses in patients with AECOPD. Here T-cell expression of CD39 measured by flow cytometry was higher in AECOPD patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…The increased CD39 expression in leukocytes could compensate for the attenuated CD39 lung expression and combat airway inflammation in COPD. Tan D et al, [ 18 ] demonstrated enhanced expression of CD39 on circulating T-cell subsets in patients with an exacerbation of COPD compared with patients with stable COPD. Our results are not at odds with those of these two previous studies; in fact they complement our current knowledge of CD39 in COPD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The increased CD39 expression in leukocytes could compensate for the attenuated CD39 lung expression and combat airway inflammation in COPD. Tan D et al, [ 18 ] demonstrated enhanced expression of CD39 on circulating T-cell subsets in patients with an exacerbation of COPD compared with patients with stable COPD. Our results are not at odds with those of these two previous studies; in fact they complement our current knowledge of CD39 in COPD.…”
Section: Discussionmentioning
confidence: 99%
“…Our study did not analyze the expression of CD39 in the pulmonary or systemic inflammatory cells. However, the increase in CD39 expression in airway and systemic inflammatory cells suggested by both articles may be the compensatory mechanism for acute exposure to tobacco [ 17 ] or infection [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with the above results, CD39 expression and activity are elevated in chronic obstructive pulmonary disease (COPD) patients by quantifying CD39 expression and soluble ATPase activity in sputum and bronchoalveolar lavage fluid cells (98). Additionally, Tan et al showed T cell-related CD39 expression is higher in acute exacerbations of COPD (AECOPD) patients than stable COPD and healthy controls (5). They prospected blocking CD39 would be a novel approach to the control of AECOPD, reducing the dependency on antibiotics.…”
Section: The Role Of Cd39 In Inflammationmentioning
confidence: 99%
“…It is now again becoming a newly recognized “immune checkpoint mediator” that interferes with antitumor or anti-inflammatory immune response (5, 6). Moreover, some recent research has revealed a number of neoteric functions of CD39, which display its close relation with Tregs (79), Th17 cells (10, 11), γδ T cells (12), and Bregs (13).…”
Section: Introductionmentioning
confidence: 99%